(untitled) (Journal Of Educational and Psychological Researches, 2025)
The current research aims to investigate the temperament styles among undergraduate students in terms of gender and specialization. A sample of 544 male and female students was chosen randomly from the University of Karbala for the academic year 2023-2024. To achieve the research objectives, the researcher adopted the scale of temperament styles by Buss-Plomin (1984) as a research tool to collect the needed data. With the help of the Statistical Package for the Social Sciences (SPSS), the research reached a number of conclusions, recommendations, and suggestions.